Automatically switched optical networks benefits and requirements. - Jaiszczyk, A.
The article summarizes driving forces that are behind automatically switched optical networks. It discusses potential features of ASONs as well as the benefits this concept may offer to carriers and their clients. The article begins with a brief discussion on limitations of existing optical networks, followed by a description of benefits of ASONs and their requirements. A numerical example illustrating the benefits of fast provisioning to the banking sector is given. Major features of ASONs are enumerated and enabling mechanisms are presented. The enabling mechanisms include discovery functions, routing, signaling, as well as protection and restoration schemes. The proposed taxonomy may facilitate understanding of a plethora of features of ASONs and their mutual relations.
Keywords: Automatically switched optical network; Banking sector; Discovery function; Enabling mechanism; Network routing; Network signaling; Protection scheme; Restoration scheme; Taxonomy